Public health responses to the HIV epidemic among black men who have sex with men: A qualitative study of US health departments and communities. - Wilson, Patrick A; Moore, Terrance E (American journal of public health, 2009)
In the United States, Black men who have sex with men (MSM) are disproportionately affected by HIV/AIDS. Thus, there is a need to understand the challenges facing health departments and community-based organizations responding to the HIV epidemic among this population. We interviewed 71 AIDS program directors, health department staff, and leaders of community-based organizations in 9 states and the District of Columbia. Participants identified psychosocial factors, a lack of capacity-building efforts, and stigma as barriers to HIV prevention responses targeting Black MSM. Participants identified culturally competent staff and culturally sensitive interventions as facilitating prevention responses. To ensure that HIV/AIDS interventions targeting Black MSM are effective, it is imperative to solicit the perceptions of frontline workers in health departments and community-based organizations.
Keywords: African Americans; Community Health Centers; Community Networks; Cultural Competency; Health Facility Administrators; Healthcare Disparities; HIV Infections; Homosexuality, Male; Humans; Male; Mental Disorders; Prejudice; Prevalence; Public Health; Public Health Administration; Self Concept; United States